1998
DOI: 10.1007/s001670050084
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar arthroscopy - indications and surgical technique

Abstract: Subtalar arthroscopy was performed in 18 patients with different diagnoses. Among standard portals the anterolateral ventral (ALV) portal was used for the arthroscope and the posterolateral dorsal (PLD) portal for instrumentation. In 4 patients the subtalar arthroscopy was used only for diagnostic purposes. In 14 patients arthroscopic surgery was carried out in the same session. The surgical procedures were partial synovectomy in 5 patients, resection of a loose body in 3 patients, a subtalar fusion in 3 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…When nonoperative treatment fails to decrease the symptoms of os trigonum syndrome, surgical excision of the os trigonum is the treatment of choice, with satisfactory clinical results reported (6)(7)(8). Excision can be performed using either an open or arthroscopic technique.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…When nonoperative treatment fails to decrease the symptoms of os trigonum syndrome, surgical excision of the os trigonum is the treatment of choice, with satisfactory clinical results reported (6)(7)(8). Excision can be performed using either an open or arthroscopic technique.…”
mentioning
confidence: 96%
“…The arthroscopic procedure has become increasingly popular to treat many ankle diseases, because it is a less invasive surgical technique with a reduced risk of complications, a shorter recovery period, and better clinical outcomes. It has also been suggested that a visible scar after open excision might influence performance for a dancer (7).…”
mentioning
confidence: 99%
“…All selected studies were identified using the literature search strategy, as the review of reference sections did not identify additional articles for inclusion. Overall, 8 studies 5 , 9 , 12 , 18 , 21 , 22 , 24 , 31 examined prone patients with 2 posterior portals (n = 111; 22.9%), 7 articles 4 , 11 , 13 , 16 , 27 , 30 , 35 evaluated lateral portals in the supine or lateral position (n = 182; 37.6%), and 5 studies 2 , 3 , 6 , 26 , 34 examined patients in the prone position with 3 portals (n = 191; 39.5%). The mean MCMS of included studies was found to be 38.4 (range, 10-63) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, arthroscopic subtalar release is minimally invasive, which facilitates early mobilisation and allows the condition of the posterior calcaneal facet to be examined. 2,[13][14][15] Parisien and Vangsness 8 demonstrated that in cases of arthrofibrosis of the subtalar joint dramatic relief of pain and an improved range of movement can be obtained after arthroscopic excision of adhesions. Elgafy and Ebraheim 13 described ten consecutive patients who underwent subtalar arthroscopy for persistent pain in the subfibular area after open reduction and internal fixation of intra-articular fractures of the calcaneum.…”
Section: Discussionmentioning
confidence: 99%